2001
DOI: 10.2136/sssaj2001.6541164x
|View full text |Cite
|
Sign up to set email alerts
|

A Soil Organic Nitrogen Fraction that Reduces the Need for Nitrogen Fertilization

Abstract: The need to estimate mineralization has long been recognized in making N fertilizer recommendations, but little progress has thus far been made in identifying a specific fraction of soil organic N that affects crop responsiveness to N fertilization. After eliminating major defects in the methodology employed to fractionate the N in soil hydrolysates, a study was conducted to compare N‐distribution analyses for soils differing in N‐fertilizer responsiveness by corn (Zea mays L.). Hydrolyses with 6 M HCl were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(70 citation statements)
references
References 28 publications
0
62
0
5
Order By: Relevance
“…This might causes ineffectiveness of inoculated Rhizobium sp. (Li et al 2009) and less response to N application (Mulvaney et al 2001). Regardless of N rates of application, all N rates of application gave significantly higher TBY than the control in both Rhizobium inoculation treatments at Hirna site.…”
Section: Total Biomass Yieldmentioning
confidence: 80%
“…This might causes ineffectiveness of inoculated Rhizobium sp. (Li et al 2009) and less response to N application (Mulvaney et al 2001). Regardless of N rates of application, all N rates of application gave significantly higher TBY than the control in both Rhizobium inoculation treatments at Hirna site.…”
Section: Total Biomass Yieldmentioning
confidence: 80%
“…Stable isotopic tracers (mainly 3 H) have shown that delivery times for surface runoff, soil water/shallow groundwater, and groundwater to river systems are on the order of months, years, and decades, respectively (Iqbal 2002;Phillips and Lindsey 2003;Sanford and Pope 2013;Tesoriero et al 2013). Incorporation of N into soil organic matter and subsequent release of this N for potential leaching to the hydrosphere is also estimated to require several years to decades (Mulvaney et al 2001;Sebilo et al 2013). Estimated magnitudes of lag time by the LVM (~11 years) and by the statistical model developed for the Mississippi River watershed (~9 years; McIsaac et al 2001) are an average of all processes delaying N delivery from the watershed to the river outlet.…”
Section: Cause Of the Lag Effect On Riverine N Exportmentioning
confidence: 99%
“…Recently, new concerns have been raised about the adverse effects of N on the environment mainly because of high application rates of N fertilizers and improper land management practices (St Luce et al 2011). Groundwater contamination by nitrates has become a worldwide concern (Mulvaney et al 2001). Thus, to improve the efficiency of N uptake by plants and reduce massive use of N mineral fertilizers, we need an accurate prediction of N supply from soil organic matter (SOM) in both natural and agricultural ecosystems (Bhogal et al 2001).…”
Section: Introductionmentioning
confidence: 99%